Menumbuhkan Minat Belajar Pada Diri Siswa Selama Mengikuti Proses Pembelajaran - Nantara, Didit (FKIP Unirow Tuban, 2021)
Learning is an interaction between students and teachers along with learning resources in a learning environment. Teachers who have high creativity and innovation will be seen in bringing student success during learning in order to achieve learning targets. To measure learning targets obtained through learning outcomes. Student learning outcomes are influenced by two factors, namely internal factors and external factors. One of the internal factors is interest in learning. A teacher is said to be professional if he is able to develop interest in students to learn. This is a challenge for a teacher to foster interest in students in participating in the learning process. Through literature review, it is known that interest in learning is the emergence of a sense of interest, attention, and having more desires in individuals without anyone pushing them to have feelings of pleasure without being forced so that changes in behavior, knowledge, and skills occur. Based on these conclusions, it is suggested that teachers are required to be enthusiastic accompanied by great creativity and innovation in fostering interest in learning in students, namely using learning methods, using learning media, using learning materials, utilizing infrastructure, and giving gifts. And it is recommended for school residents to do the same in fostering student interest in learning so that all lessons taught in class do not become a scourge.